Answer:
Step-by-step explanation:
Hello
A (5;2)
B (-1;-7)
y = ax + b
2 = 5a + b
-7 = -a + b
2 - (-7) = 5a - (-a) + b - b
2 + 7 = 5a + a
9 = 6a
a = 9/6
a = 3/2
2 = 3/2 * 5 + b
b = 2 - 15/2
b = 4/2 - 15/2
b = 11/2
y = 3/2 x + 11/2
y+1= 3/2(x-4)
y + 1 = 3/2 x - 6
y = 3/2 x - 6 - 1
y = 3/2 x - 7 => no
y-4= 3/2(x+1)
y - 4 = 3/2 x + 3/2
y = 3/2 x + 3/2 + 4
y = 3/2 x + 3/2 + 8/2
y = 3/2 x + 11/2 => yes
y+4= 3/2(x-1)
y + 4 = 3/2 x - 3/2
y = 3/2 x - 3/2 - 4
y = 3/2 x - 3/2 - 8/2
y = 3/2 x - 11/2 => no
y-1= 3/2 (x+4)
y - 1 = 3/2 x + 6
y = 3/2 x + 6 + 1
y = 3/2 x + 7 => no
So there are 12 spaces right. In first blank u have a choice to fill any of the alphabet .(first twelve alphabets) <span>and it goes down to just 1 letter in the last space. but do i just multiply them.
hope dis helps</span>
Answer:
25 cm
Step-by-step explanation:
a^2 + b^2 = c^2
7^2 + 24^2 = c^2
49 + 576 = c^2
c^2 = 625
c = 25
Answer: 25 cm
Answer:
5.7
Step-by-step explanation:
sine cosine tangent
soh cah toa
sine = opposite/hypotenuse
so sin(35)= x/10
you can multiply 10 to both sides to get rid of the 10 denominator on the right leaving you with 10sin(35)=x
be sure your calculator is in degrees.
put that into a calculator leaving you with 5.7
Answer:
Step-by-step explanation:
4x^2 is the quadratic
3x is linear
-6 is the constant.